1997
DOI: 10.1126/science.276.5311.384
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Materials: Self-Organized Nanostructures

Abstract: Miniaturized triblock copolymers have been found to self-assemble into nanostructures that are highly regular in size and shape. Mushroom-shaped supramolecular structures of about 200 kilodaltons form by crystallization of the chemically identical blocks and self-organize into films containing 100 or more layers stacked in a polar arrangement. The polar supramolecular material exhibits spontaneous second-harmonic generation from infrared to green photons and has an adhesive tape-like character with nonadhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
661
1
12

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,079 publications
(688 citation statements)
references
References 14 publications
9
661
1
12
Order By: Relevance
“…1 In particular, the selfassembly of organic molecules and synthetic polymers have been extensively investigated in recent years. 2,3 These studies reported nanoscale to microscale morphologies such as spherical or cylindrical micelles, vesicles, ribbons, fibers, bowls, and toroids. [4][5][6][7][8][9] Of particular interest are stimuli-responsive materials that allow for the directed or modulated self-assembly on the nanoscale in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…1 In particular, the selfassembly of organic molecules and synthetic polymers have been extensively investigated in recent years. 2,3 These studies reported nanoscale to microscale morphologies such as spherical or cylindrical micelles, vesicles, ribbons, fibers, bowls, and toroids. [4][5][6][7][8][9] Of particular interest are stimuli-responsive materials that allow for the directed or modulated self-assembly on the nanoscale in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Here, systematic and iterative studies on designed systems will be very useful to emulate the biological self-assembly in artificial systems. Our laboratory has had this focus over the past decade, seeking to develop self-assembly codes for function in macromolecular scales (Stupp et al 1997;Hartgerink et al 2001;Zubarev et al 2001Zubarev et al , 2006. In analogy to polymers, we define the scale as that of molecular assemblies in which the collective molar mass exceeds 10 4 daltons.…”
Section: Introductionmentioning
confidence: 99%
“…Although amphiphilic diblock copolymers are usually used to produce aqueous micelles, ABC triblock copolymers have the advantage to form more complex nanostructures [4][5]. In this respect, well-defined coreshell-corona (CSC) micelles have been prepared from poly(styrene)-block-poly(2-vinylpyridine)-blockpoly(ethylene oxide) (PS-b-P2VP-b-PEO) triblock copolymers [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%